2021
DOI: 10.3390/en14030659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soiling on Solar Photovoltaic Performance under Desert Climatic Conditions

Abstract: The solar irradiation at the gulf Arabia is considered one of the highest in the world. However, this region is classified as a desert with high dust accumulation. Thus, the objective of this study is to analyze the effect of soiling and the photovoltaic (PV) tilt angle on the performance of 2.0 MWp of car park PV plant in Oman. Experimental measurements were taken and a model was developed for simulation. The power generation by the cleaned PV system was measured as 1460 kW around noon. After one week of oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Investors utilise the data obtained from their independent consulting engineer during the feasibility study, or the engineering, procurement and construction (EPC) companies when the tenderer submits their proposal during the tender process to determine the financial viability and ROI of a PV system [50]. In South Africa, the estimated electricity yield is obtained by simulating the PV system, and the operating conditions thereof, using software such as HelioScope and PVSyst [57][58][59]. As part of the terms and conditions of the contractual agreement, yield warranties are agreed upon.…”
Section: Design Characteristics Of the Case Studymentioning
confidence: 99%
“…Investors utilise the data obtained from their independent consulting engineer during the feasibility study, or the engineering, procurement and construction (EPC) companies when the tenderer submits their proposal during the tender process to determine the financial viability and ROI of a PV system [50]. In South Africa, the estimated electricity yield is obtained by simulating the PV system, and the operating conditions thereof, using software such as HelioScope and PVSyst [57][58][59]. As part of the terms and conditions of the contractual agreement, yield warranties are agreed upon.…”
Section: Design Characteristics Of the Case Studymentioning
confidence: 99%
“…Bhaduri and Kottantharayil (2018) also proved that the soiling effect affects 16-18% of the efficiency. In Kazem, Chaichan, Al-Waeli, and Sopian (2020), panels' daily power losses and monthly efficiency reduction due to dust in some places are more than 1% and 80%, respectively Siyabi, Mayasi, Shukaili, and Khanna (2021). A study on the effect of dust in Oman concluded that 7.5% of the dust in the environment reduces electricity production by 5.6% in a month, and 12.5% of dust reduces 10.8% of electricity Gives results.…”
Section: Introductionmentioning
confidence: 99%
“…The power plant operators regularly calculated the theoretical electricity production based on the radiation data typical of the area. There was often a discrepancy of more than 10% between the measured data and the expected values [6][7][8][9]. To find out the reasons, thermography assessments were made on several occasions [10,11].…”
Section: Introductionmentioning
confidence: 99%